Video coding techniques for networks - LIU Wei; MA Zheng-ming (Tongxin xuebao)
Due to the increasing demands on video services over Internet, video-coding techniques suitable for network has drawn tremendous attention in both academia and industry. The purpose of our study was summarizing the developing of video coding techniques for networks. We gave a particular description of the primary video coding schemes over Internet. We put emphasis on scalable coding techniques and MD coding techniques. After description, we made comparison, and further discussed the possibility of the combination of these techniques.